2008
DOI: 10.1111/j.1365-294x.2008.03977.x
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic structure in Atlantic and Pacific Ocean common murres (Uria aalge): natural replicate tests of post‐Pleistocene evolution

Abstract: Understanding the factors that influence population differentiation in temperate taxa can be difficult because the signatures of both historic and contemporary demographics are often reflected in population genetic patterns. Fortunately, analyses based on coalescent theory can help untangle the relative influence of these historic and contemporary factors. Common murres (Uria aalge) are vagile seabirds that breed in the boreal and low arctic waters of the Northern Hemisphere. Previous analyses revealed that At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 63 publications
3
59
0
Order By: Relevance
“…Recent multi-locus studies of the Common Murre phylogeography showed lack of geographical structuring and low mtDNA diversity across the North Pacific (Friesen and Piatt, 2003;Morris-Pocock et al, 2008). Our results are consistent with these findings.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Recent multi-locus studies of the Common Murre phylogeography showed lack of geographical structuring and low mtDNA diversity across the North Pacific (Friesen and Piatt, 2003;Morris-Pocock et al, 2008). Our results are consistent with these findings.…”
Section: Discussionsupporting
confidence: 92%
“…Mantel's test showed no correlation between genetic and geographical distances among the seven breeding colonies sampled (r 2 ¼0.08; P¼0.127). These data, as well as the results of two multi-locus studies (Friesen and Piatt, 2003;Morris-Pocock et al, 2008), justify grouping all live birds into a single unit for the following analysis of mtDNA diversity and haplotype frequencies. The MK test identified an excess of non-synonymous substitutions among polymorphic sites within species (Fisher's exact P¼0.004) suggesting purifying selection.…”
Section: Resultsmentioning
confidence: 95%
“…In particular, little or no genetic differentiation between populations has been reported for other alcids inhabiting the Arctic, e.g., Atlantic puffin (Fratercula arctica, Moen 1991), Atlantic subspecies of Brünnich's guillemot (Birt-Friesen et al 1992;Morris-Pocock et al 2008), common guillemot (Moum et al 1991; 1996; Moum and Arnason 2001;Riffaut et al 2005), and marbled murrelet (Brachyramphus marmoratus, Congdon et al 2000;Friesen et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Pereira & Baker 2008, Jesus et al 2009, Patterson et al 2011, population differentiation (e.g. Morris-Pocock et al 2008, Gómez-Díaz et al 2009, Hailer et al 2011; see review by Friesen et al 2007b) and hybridization (e.g. Pacheco et al 2002, Gay et al 2007, 2008b, Taylor et al 2010b, and to estimate population parameters such as migration rates or population sizes (e.g.…”
Section: Molecular Genetic Methodsmentioning
confidence: 99%
“…However, as in phylogenetic studies, the genetic basis of morphological and behavioural characters is not usually known (but see Baião et al 2007): even if individuals or populations are morphologically similar, they may differ genetically (e.g. Friesen et al 1996a, Morris-Pocock et al 2008, Hailer et al 2011.…”
Section: Population Genetics and Phylogeographymentioning
confidence: 99%